Strategic issue management - Ansoff, H. Igor (Strategic Management Journal, 1980)
Abstract The paper presents a systematic approach for early identification and fast response to important trends and events which impact on the firm. Two versions of such an approach are described: a strong signal and a weak signal strategic issue management system . Strategic issue management, which responds to signals in “real time”, is compared to periodic strategic planning, and criteria for choice among the three are proposed.